2017
DOI: 10.1002/jmv.24757
|View full text |Cite
|
Sign up to set email alerts
|

Detection of D151G/N mutations in the neuraminidase gene of influenza A (H3N2) viruses by real‐time RT‐PCR allelic discrimination assay

Abstract: Single nucleotide polymorphisms (SNPs) at D151 position of neuraminidase (NA) gene of influenza A (H3N2) virus has been associated with drug resistance and increased binding affinity. NA-D151G/N-substitutions of influenza A (H3N2) viruses are frequently induced and selected by culturing in Madin-Darby canine kidney (MDCK) cell lines. It is important to consider and exclude D151G/N mutants after isolation of influenza virus in MDCK cell line; since, the substitutions can highly influence the results of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For the different results of clinical specimens by CMT and FMT, an influenza A real-time RT-PCR detection kit was also used to detect influenza A again [21]. The results revealed that 26 of the 33 specimens that detected negative with CMT but positive with FMT, detected positive with the real-time RT-PCR detection method, and none of the 3 specimens that had previously detected positive with CMT but negative with FMT provided a positive result (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…For the different results of clinical specimens by CMT and FMT, an influenza A real-time RT-PCR detection kit was also used to detect influenza A again [21]. The results revealed that 26 of the 33 specimens that detected negative with CMT but positive with FMT, detected positive with the real-time RT-PCR detection method, and none of the 3 specimens that had previously detected positive with CMT but negative with FMT provided a positive result (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, HA Q226L [19][20][21] and G186V [19,[22][23][24] mutations were shown to increase the affinitive binding between H7N9 viruses and human-type receptors. Moreover, recent studies showed that N2 with a D151G amino acid substitution [25][26][27], or N1 with a G147R amino acid substitution [26,28,29], had similar properties of enhanced affinitive binding for SA receptors. However, further investigation is required to explore whether the pathology of H7N9 infections could be caused by other amino acid substitutions, resulting from unknown conformational variations in dual-receptor binding capacity of the H7 protein, or additional affinity owing to the N9 protein.…”
Section: Introductionmentioning
confidence: 99%